(untitled) (Journal of Social Sciences Review, 2022)
The main theme of the study is to determine the impact of parental support on the sports participation of the student-athletes (male & female) at Universities level Khyber Pakhtunkhwa Pakistan. The survey modal approach was selected in the present study. Total 284 male and 125 female student-athletes were included in this study. The researcher has used 5 question form of personal information for getting the demographic features of the participants and also used adapted scale of Sports participation developed by Diane De Gill to analyze the parental approach towards the sports participation of their children (Gill, Gross, & Huddleston, 1983). According the results, the participation of male student-athletes were reported more than female student-athletes. The study has concluded that male student-athletes receive more social, emotional and financial support from their parents in term of sports participation as compared to female student-athletes.